(untitled) (Temas de Nuestra América Revista de Estudios Latinoaméricanos, 2018)
Politics and Social Change in Latin America: the Distinct Tradition Political Change in Central America. Internal and External Dimensions The End and the Beginnig: the Nicaraguan Revolution Revolution in Central America